Molecular insights into Sertoli cell function: how do metabolic disorders in childhood and adolescence affect spermatogonial fate? - Rossella Cannarella; Roberto Curto; Rosita A. Condorelli; Scott D. Lundy; Sandro La Vignera; Aldo E. Calogero (Nature Communications, 2024)
Abstract Male infertility is a major public health concern globally with unknown etiology in approximately half of cases. The decline in total sperm count over the past four decades and the parallel increase in childhood obesity may suggest an association between these two conditions. Here, we review the molecular mechanisms through which obesity during childhood and adolescence may impair future testicular function. Several mechanisms occurring in obesity can interfere with the delicate metabolic processes taking place at the testicular level during childhood and adolescence, providing the molecular substrate to hypothesize a causal relationship between childhood obesity and the risk of low sperm counts in adulthood.